On Approval of the Concept of Education of Youth in the Spirit of Military and Patriotism (Journal of Pedagogical Inventions and Practices, 2022)
There was a talk about increasing and intensifying the effectiveness of work on educating young people in the spirit of military patriotism, and you were briefed on what changes have been made. The concept was discussed in order to increase respect for the Fatherland